Ethnicity‐specific obesity cut‐points in the development of Type 2 diabetes – a prospective study including three ethnic groups in the United Kingdom. Issue 2 (1st October 2014) - Tillin, T.; Sattar, N.; Godsland, I. F.; Hughes, A. D.; Chaturvedi, N.; Forouhi, N. G.
Abstract Aims Conventional definitions of obesity, e.g. body mass index (BMI) ≥ 30 kg/m2 or waist circumference cut‐points of 102 cm (men) and 88 cm (women), may underestimate metabolic risk in non‐Europeans. We prospectively identified equivalent ethnicity‐specific obesity cut‐points for the estimation of diabetes risk in British South Asians, African‐Caribbeans and Europeans. Methods We studied a population‐based cohort from London, UK (1356 Europeans, 842 South Asians, 335 African‐Caribbeans) who were aged 40–69 years at baseline (1988–1991), when they underwent anthropometry, fasting and post‐load (75 g oral glucose tolerance test) blood tests. Incident Type 2 diabetes was identified from primary care records, participant recall and/or follow‐up biochemistry. Ethnicity‐specific obesity cut‐points in association with diabetes incidence were estimated using negative binomial regression. Results Diabetes incidence rates (per 1000 person years) at a median follow‐up of 19 years were 20.8 (95% CI: 18.4, 23.6) and 12.0 (8.3, 17.2) in South Asian men and women, 16.5 (12.7, 21.4) and 17.5 (13.0, 23.7) in African‐Caribbean men and women, and 7.4 (6.3, 8.7), and 7.2 (5.3, 9.8) in European men and women. For incidence rates equivalent to those at a BMI of 30 kg/m2 in European men and women, age‐ and sex‐adjusted cut‐points were: South Asians, 25.2 (23.4, 26.6) kg/m2; and African‐Caribbeans, 27.2 (25.2, 28.6) kg/m2. For South Asian and African‐Caribbean men, respectively, waist circumference cut‐points of 90.4 (85.0, 94.5) and 90.6 (85.0, 94.5) cm were equivalent to a value of 102 cm in European men. Waist circumference cut‐points of 84.0 (74.0, 90.0) cm in South Asian women and 81.2 (71.4, 87.4) cm in African‐Caribbean women were equivalent to a value of 88 cm in European women. Conclusions In prospective analyses, British South Asians and African‐Caribbeans had equivalent diabetes incidence rates at substantially lower obesity levels than the conventional European cut‐points.